Personal agreement and its relationship to the practice of sports at the University Comparative study (Journal of the College of Basic Education, 2023)
University education has become a field for many studies that focused on youth problems.University students constitute the main element in the most important segment of society, which is the youth.These problems can affect the level of psychological, social, health, family, and academic adjustment of the students.Numerous studies have confirmed that university students are exposed to many problems of mismatch. WhyPersonal compatibility was one of the goals that the university seeks to achieve because of its